Design and Performance Analysis of Building Monitoring System withWireless Sensor Networks - Abdala, Mohammed; Salih, Alaa (Iraqi Journal of Science, 2024)
The Wireless Sensor Network (WSN) provides a potential technique formonitoring the indoor environment. The proposed system consists of severalwireless sensor nodes that are deployed in a building in addition to a local serverhosting web base application for storing sensing data. The widely adopted standardfor wireless sensor network platform is the IEEE 802.15.4/ ZigBee. It is consideredas the “technology of choice” due to low-power, cost-effective communication andthe reliability it provide. This paper will simulate and explore the performance ofZigBee using OPNET Modeler 14.5. The paper will study and analyze variousparameters that include changing the network topology, number of nodes anddifferent performance parameters such as network delay, throughput, and others.The web base application is designed to interact with a WSN, allowing a user toconsult sensor states and receive sensor alerts. Sensor alerts will be received when asensor's threshold value exceeds the limit. Therefore, the user will be notifiedwhenever there are changes in the WSN. The web base application system allowsthe manager or owner of building to remote monitoring sensing data via Internet byusing a web browser.